Covert violence: the secret weapon of the powerless - Levin, Jack (Bristol University Press, 2023)
Covert violence occurs in all social institutions--including families and close relationships, education, workplaces, politics, mass media and healthcare--each with its own unique power dynamics that shape the incidence and patterns of these vicious acts. This book focuses on the types of surreptitious murder and mayhem that perpetrators intend to go unnoticed by would-be victims--until it's too late. When such attacks are carried out with efficiency and competence, they may be disguised in official records as the result of illness, accident or intentional self-harm, only on occasion to be later reclassified as the brutal crimes they are. This compelling and much-needed book is for all those who seek to understand--and strive to prevent--violence in society